PENGARUH PROMOSI, PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI DIGITAL CARD BY.U DI KOTA - Hartini Hartini; Moh Afifulloh Syaekhun (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Given the scale of the use of data packets in Indonesia to add ourh great opportunities for telecommunications companies. Telkomsel as the largest internet service provider in Indonesia at the end of 2019 launched a new product called by.U which is now starting to be used by people in various regions, one of which is in the city of Sumbawa. The challenge for new products is to attract buying interest in these products, one of which is through promotion. Price strategy and product quality. This study aims to determine whether promotion, price perception and product quality affect the interest in buying digital cards by.U in the city of Sumbawa. Collecting data in this study using a questionnaire distributed to 100 respondents who were taken based on purposive sampling technique. The data were analyzed using descriptive quantitative analysis. The results showed that the independent variables of promotion, price perception and product quality had a partial effect on the dependent variable of interest in buying digital cards by.U in the city of Sumbawa